2022-RA-1020-ESGO Family history in BRCA mutation carriers affected by breast and ovarian cancer and its role in identifying subjects at high risk - Negri, Serena; de Ponti, Elena; Sina, Federica Paola; Sala, Elena; Dell’Oro, Cristina; Roversi, Gaia; Lazzarin, Sara; Marchette, Martina Delle; Inzoli, Alessandra; Toso, Claudia; Fumagalli, Simona; Campanella, Ornella; et al. (International journal of gynecological cancer, 2022)
Introduction/BackgroundBRCA1 and BRCA2 mutations are the most common cause of hereditary breast and ovarian cancer, and are also associated with an increased risk of prostate and pancreatic cancer.Many guidelines have been provided over time to identify BRCA mutation carriers, and they are usually based on a suggestive personal and family history (FH) of cancer. Addressing affected patients to genetic counseling can lead to therapeutic benefits, however identifying healthy high risk individuals before they develop cancer could give them the opportunity to access appropriate surveillance and risk-reducing treatments.MethodologyWe applied the family history (FH) criteria proposed by the National Comprehensive Cancer Network (NCCN) Clinical Practice Guidelines in Oncology (NCCN Guidelines®) and the Italian Association of Medical Oncology (AIOM) guidelines to the FH of 157 women who found out to be BRCA mutations carriers after a diagnosis of breast or ovarian cancer.ResultsA FH of BRCA-related cancer was found in almost 85% of women. NCCN and AIOM FH criteria would have detected 63.6% and 52.2% of patients respectively before tumor diagnosis (p<0,05). The most frequent criteria were a FH of ovarian cancer and of breast cancer diagnosed <45 years old. 65% of the women who died from progression of disease would have been eligible for testing based on their FH.ConclusionFamily history should always be investigated and specific sets of criteria should be included in guidelines independently from a personal history of cancer.